Rain attenuation statistics for mobile satellite communications estimated from radar measurements in Malaysia - Mohammad Ibrahim Abozeed; Manhal Alhilali; Lam Hong Yin; Jafri Din (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Mobile satellite communications will play a significant role in the next 5th generation mobile services. The use of high-frequency bands will be the enabler of this advancement. However, at high frequencies, excess rain attenuation causes severe signal losses and presents a major threat for the system availability, especially in the tropical region. To that end, this study presents the rain attenuation impact on mobile satellite communications estimated using long-term radar measurements in Malaysia, by exploiting the horizontal structure of rain from the radar database and simulating inner-city and highway mobile terminals scenarios. Additionally, a scaling factor was presented to scale available fixed satellite terminals measurements to mobile terminals operating at the same locality under similar conditions. In comparison to the available link measurements, the radar database was reliable enough to provide highly accurate estimates. In all simulation scenarios, the mobile terminal will depart the rainy area soon enough and experience lower attenuation statistics in comparison with the fixed terminal. The provided results will help determine the overall future system performance, especially in tropical regions.